O warsztatach tkackich w starożytnym Rzymie słów kilka - Kaczmarek, Zofia (Studia Europaea Gnesnensia, 2012)
The most important source for the research into weaving products are excavated fabrics. By defining its weave, spin direction of the thread, raw materials used or the employed dyestuff the origin of the fabric may be determined, as well as the loom on which it was weft. Iconography is also greatly useful in the reconstruction of weaving work. The first loom known inRomewas the vertical warp-weighted loom. This loom, despite offering the possibility of weaving very broad fabrics, quickly went out of use inItaly, probably because weaving on it requires earlier preparation, such as weaving the starting border. Also, we do not know any representation of this type of loom in Roman art. The vertical two-beam loom resembles the warp-weighted loom, with the exception that the row of weights is replaced with a horizontal beam. It is easier to use, as it does not require preliminary work, so weaving can be begun at once. We also know representations of this loom in Roman art, which facilitate the reconstruction of its use in antiquity. The most interesting issue is the question of familiarity with the horizontal loom. The written sources do not mention it, nor is there any representation in art that we know of, therefore we must rely on what the fabrics themselves present. However, one may venture a claim that the more complicated the pattern, the greater the likelihood of the horizontal loom having been used. Furthermore, its knowledge might be attested to by the contents of Diocletian’s edict. One cannot underestimate the evidence for the existence of a horizontal loom, yet it should be assumed that it had not been introduced on a wide scale. Consequently, it appears that the Romans made use primarily of vertical looms, with the prevalence, from the turn of of the two-beam loom.